CHRND mutation causes a congenital myasthenic syndrome by impairing co-clustering of the acetylcholine receptor with rapsyn. - Müller, J; Baumeister, S; Schara, U; Cossins, J; Krause, S; von der Hagen, M; Huebner, A; Webster, R; Beeson, D; Lochmüller, H; Abicht, A (2006)
The objective of this study was to analyse the mutations of the acetylcholine receptor (AChR) delta subunit gene (CHRND) in a patient with sporadic congenital myasthenic syndrome (CMS). Mutations in various genes encoding proteins expressed at the neuromuscular junction may cause CMS. Mutations of AChR subunit genes lead to end-plate AChR deficiency or to altered kinetic properties of the receptor. Mutations in the alpha, beta and delta subunits of the AChR are less frequent than mutations of the epsilon subunit; mutations in these subunits leading to AChR deficiency are often associated with a severe phenotype. A sporadic patient from Germany was studied, who presented with an early onset CMS associated with feeding difficulties, ptosis, a moderate general weakness responsive to anticholinesterase treatment and recurrent episodes of respiratory insufficiency provoked by infections. The CHRND gene was screened for mutations by RFLP, long-range PCR and sequence analysis. Subsequently, we conducted functional studies of AChR mutants co-transfected with rapsyn in HEK 293 cells. Heterozygously to a 2.2 kb microdeletion disrupting the CHRND gene, we identified a novel point mutation in the long cytoplasmic loop, CHRND E381K. The cytoplasmic loop of the AChR subunits is known to be essential for AChR-rapsyn co-clustering. We therefore studied the interaction of AChR containing the CHRND E381K mutation with rapsyn by evaluating expression and co-localization of rapsyn and mutated AChR subunits in co-transfected HEK 293 cells. Interestingly, the mutated receptor showed severely reduced cluster formation compared with the wild-type receptor. In contrast, the corresponding amino acid substitution in the cytoplasmic loop of the AChR epsilon (CHRNE E376K) as well as a recently reported CMS mutation affecting this domain (CHRNE N436del) had no impact on cluster formation. CHRND mutations are a rare cause for CMS but should be considered in patients with a severe, early onset disease form, clinically resembling a rapsyn phenotype with recurrent episodic apnoeas. Our results suggest that impairment of AChR-rapsyn co-clustering--a well-known molecular mechanism for rapsyn mutations--could also result from mutations in the delta subunit. Introduction of the same mutation in the epsilon subunit had no effect on AChR clustering indicating a special role of the delta subunit in AChR-rapsyn interactions.